Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
Quantitative Predictions of Standart Modell Parameters from Spiral Geometry in Helix Light Vortex Theory
Quantitative Predictions of Standart Modell Parameters from Spiral Geometry in Helix Light Vortex Theory